SOSIALISASI PROGRAM PENGEMBANGAN KELOMPOK BERMAIN DI KB KASIH IBU DESA DUANO KEC.SUWAWA TENGAH KAB.BONE BOLANGO - Sulastya Ningsih (Civic Education Law and Humaniora : Jurnal Pengabdian Masyarakat Terintegrasi, 2024)
Early Childhood Education (PAUD) plays an important role in optimizing the growth and development of children in their golden age, especially for children aged 2 to 6 years. Among the various PAUD services, Playgroups (KB) are designed to provide holistic education that emphasizes the physical-motor, cognitive, language, social-emotional, art, and religious values of early childhood. KB is particularly focused on children aged 3 and 4 years, where learning experiences are structured to be meaningful and relevant. Every activity, whether related to environmental exploration, creative play, or interaction with peers, is seen as a valuable opportunity for child development. This community service initiative aims to socialize and implement a comprehensive learning program at the Kasih Ibu Playgroup, ensuring that both teachers and parents are well-informed and equipped to provide the best support for their children's early learning. By encouraging a more collaborative and informed approach to early childhood education, this program seeks to improve the overall quality of education and contribute to the holistic development of children in this community.Keywords: Playgroup; Early Childhood.